Abstract: Harnessing evidence and knowledge to move to practice - Crawford, Joanne (New Zealand Journal of Health and Safety Practice, 2024)
The use of evidence by those involved in health and safety practice is at times sporadic with knowledge often kept behind paywalls and practitioners being unable to access it. There are additional problems with a gap between research within tertiary institutions being focused on single issue problems and the timing of research projects. This adds to the at times difficult, development of workplace interventions in a complex work environment. This presentation will highlight some of those issues around enabling translation of research into practice and talk about the pilot project, the Wellbeing at Work Hub. The Hub, based on a “what works” centre design was developed to take research evidence, synthesise it into a series of principles that can then be applied in practice. However, our immediate learnings from the pilot are that of credibility, thus any items shared have to be tested and validated through a systematic approach. While the hub pilot has been completed and we continue to build the hub, there is a need for further engagement involving stakeholders, industry, researchers and practitioners to identify the research questions that need to be addressed. The development of a research/practitioner network at VUW is ongoing and taking the example from Canada, where networks work together to co-design research which is both useful and doable. Working together we can build that evidence base, drawing from international research and building our own local research knowledge; with the aim of influencing and improving practice.